Life expectancy and entropy values for workers of Pachycondyla striata (Hymenoptera: Formicidae: Ponerinae) - Da Silva-Melo, Adolfo [UNESP] (2011)
We investigated the life expectancy and entropy value for workers of the ant Pachycondyla striata. Seven nests were excavated and these colonies were raised in laboratory conditions. The workers have a mean life-span of 74.48 days, these have a high mortality rate in the period of 1 to 85 days with a high entropy value of H = 0.611, confirming the number of deaths in the initial period.